An intelligent protection scheme based on support vector machine for fault detection in microgrid using transient signals in protection scheme - Tiwari Shankarshan Prasad (Serbian Journal of Electrical Engineering)
Fault detection in the microgrid is a crucial task due to the diversified fault conditions, and it must be rapidly identified to reduce any serious hindrance to the system. The fault current behaviour due to change in fault resistance of the touching point can damage the switches of integrated converters. In addition to the above, sporadic conditions can also affect the profile of voltage and current, in the system. Traditional protection schemes need modification to prevent relay maloperation of the microgrid. This paper presents a protection scheme based on support vector machines to detect faults under such tedious conditions. In this protection scheme, acquired samples of voltage and current from selected bus have been used and processed through the data processing tool discrete wavelet transform. The protection scheme is operating in two dissimilar operating modes, where initially mode was identified then fault detection/classification was done. Section identification task was performed to identify faulty sections under varying operating scenarios. The uncertain conditions of the renewable sources can affect the performance of the system, therefore some random cases have been considered to validate the protection scheme.